2020
DOI: 10.1097/acm.0000000000003094
|View full text |Cite
|
Sign up to set email alerts
|

Redesigning the Learning Environment to Promote Learner Well-Being and Professional Development

Abstract: There is a high prevalence of burnout and depression among medical students and residents (or learners), which can negatively impact them personally, their professional development, and the patients to whom they provide care. Educators have a responsibility for the system-level factors that influence learners’ well-being. In this Invited Commentary, the authors outline strategies institutions and affiliated training sites responsible for educating learners can take to pursue the recommended goal related to lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 28 publications
0
54
0
2
Order By: Relevance
“…Improvements in wellbeing metrics of resilience, stress, and satisfaction with life accompanied the above educational gains. This is noteworthy because equipping the next generation of medical and graduate students with tools to decrease stress and improve resilience-two major features of burnout-is of great interest to the academic community (30)(31)(32). Moreover, a greater satisfaction with life among students is paramount to education as a whole and is a cornerstone for cultivating scientific excellence in a wellness environment (33).…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in wellbeing metrics of resilience, stress, and satisfaction with life accompanied the above educational gains. This is noteworthy because equipping the next generation of medical and graduate students with tools to decrease stress and improve resilience-two major features of burnout-is of great interest to the academic community (30)(31)(32). Moreover, a greater satisfaction with life among students is paramount to education as a whole and is a cornerstone for cultivating scientific excellence in a wellness environment (33).…”
Section: Discussionmentioning
confidence: 99%
“…42 The diagnosis of an institution’s LE using tools such as JHLES and MSLES can result in clinical and administrative implications, in a sense that health educators can map their medical school’s problem and act to minimize it, supporting medical students, training medical teachers, and modifying the curriculum as needed. 43…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although responses were more diverse, a majority of students indicated that the format adopted reduced stress in learning. We plan to repeat and extend this survey in future years but, even within the limitations of parametric analysis of the Likert format (Sullivan & Artino, 2013), these data provide support for the idea that a Clinical/Anatomical approach and reduction of detail in initial learning can mitigate the deleterious effects of student stress (Dyrbye et al, 2019).…”
Section: Discussionmentioning
confidence: 88%
“…Compression of the duration of instruction in anatomical sciences has been particularly disadvantageous and stressful for students with limited prior training as it requires simultaneous acquisition of the vocabulary and “grammar” of medicine (Bowen & ten Cate, 2017; Wilson‐Anstey, Lambert, & Krog, 2019). The increase in student stress has recently been recognized as a major problem, with consequences in rising rates of attrition, alcohol dependency and even suicide among medical students (Dyrbye, Lipscomb, & Thibault, 2019; Dyrbye, Thomas, & Shanafelt, 2005; Hill, Goicochea, & Merlo, 2018; Jackson, Shanafelt, Hasan, Satele, & Dyrbye, 2016; Laitman & Muller, 2019). However, few studies have proposed specific methods for modifying medical curricula to decrease student stress.…”
Section: Introductionmentioning
confidence: 99%